2023
DOI: 10.1002/gcc.23121
|View full text |Cite
|
Sign up to set email alerts
|

circPVT1andPVT1/AKT3show a role in cell proliferation, apoptosis, and tumor subtype‐definition in small cell lung cancer

Abstract: Small cell lung cancer (SCLC) is treated as a homogeneous disease, although the expression of NEUROD1, ASCL1, POU2F3, and YAP1 identifies distinct molecular subtypes. The MYC oncogene, amplified in SCLC, was recently shown to act as a lineage-specific factor to associate subtypes with histological classes. Indeed, Doron Tolomeo and Debora Traversa contributed equally to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 84 publications
(171 reference statements)
0
8
0
Order By: Relevance
“…Further experiments show that circPVT1 inhibited the degradation of AEG-1 (Astrocyte Elevated Gene 1) by binding to miRNA-30b-5p. The oncogene AEG-1 was demonstrated that it could regulate the expression of genes associated with breast cancer malignant progression [13]. Our data suggest that circPVT1 is a key regulator of AEG-1 in the breast cancer and might be a novel biomarker target for breast cancer diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Further experiments show that circPVT1 inhibited the degradation of AEG-1 (Astrocyte Elevated Gene 1) by binding to miRNA-30b-5p. The oncogene AEG-1 was demonstrated that it could regulate the expression of genes associated with breast cancer malignant progression [13]. Our data suggest that circPVT1 is a key regulator of AEG-1 in the breast cancer and might be a novel biomarker target for breast cancer diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 68%
“…CircPVT1 is located on chromosome 8q24 and plays a carcinogenic role in a variety of cancers, including lung cancer, head and neck cancer, and oral squamous cell carcinoma [5,6,7]. Several studies found circPVT1 might exert an oncogenic effect in cancer cells by stabilizing c-Myc protein expression [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, we have recently demonstrated an oncogenic role in vitro for the PVT1::AKT3 chimera, transcribed from a fusion gene mapping on an HSR in the MYC -amplified SCLC cell line GLC1HSR [ 22 ]. Indeed, its silencing decreased cell proliferation and increased apoptosis [ 113 ].…”
Section: Methods and Bioinformatic Tools To Detect Genomic Amplificat...mentioning
confidence: 99%
“…Consistently, circPVT1 was also found upregulated in several cancers, such as bladder cancer, oral squamous cell carcinoma, and small cell lung cancer, highlighting its relevance in cancer progression. [ 368 – 370 ] . Another circRNA involved in the regulation of metastasis in different tumor types, including OS, is circUBAP2 [ 371 374 ].…”
Section: Cernets Involving Circrnasmentioning
confidence: 99%